THE EFFECT OF SILVY PASTURAL SYSTEMS ON CARRYING CAPACITY AND SOIL PROPERTY OF GRASS LAND - SUKRISTIYONUBOWO, .; WIGENA, I GEDE PUTU; TUHERKIH, E.; MARYAM, .; SANTOSO, D. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2000)
This experiment was the last activity of soil-crop management experiment to improve quantity and quality of fodder of grass land. This experiment has been carried out since 1994/1995 cropping season in Selengen Village, Lombok 8arat District, West Nusa Tenggara. In 1998/1999 the observation was focused on carrying capacity and soil properties. Feeding through grazing and cut and carry was applied to measure the carrying capacity. The experiment used randomized complete block design and the treatments  were arranged to split split plot design replicated four times. The main-plot treatments were (1) with wind breaker and (2) without wind breaker. The sub-plot treatments were four combinations of native grass land, introduced grass, and introduced legume: (A) native grass land, (B) native grass land + Paspalum sp.,(C) native grass land + Arachis gambrara, and (D) native grass land + Paspalum sp. + Arachis gambrara. The sub-sub-plot treatments were (a) grazing and (b) cut and carry. Furthermore the combination between treatments with wind breaker (1) and native grass land +Paspalum sp. +Arachis gambrata (D) was called silvy-pasture system, while the combination between treatments without wind breaker (2) and native grass land (A) was named native grass land. The results indicated that the highest fresh fodder production and carrying capacity both for the first and second harvesting were shown by the silvy-pasture system. The yields were 35.01 and 28.47 t/ha for the first and second harvesting, respectively. Meanwhile, the carrying capacity of the first harvesting using grazing and cut and carry were 1.47 and 1.75 cattle/ha/year with increasing life weights were 0.46 and 0.29 kg/day, respectively. For the second harvesting, the carrying capacities were 1.10 and 1.16 cattle/ha/year with increasing life weight about 0.28 kg/day, respectively. Introduction of Paspalum sp. and Arachis gambrata significantly improved carrying capacity of native grass land.